2016
DOI: 10.18632/oncotarget.9573
|View full text |Cite
|
Sign up to set email alerts
|

JMJD2B is required forHelicobacter pylori-induced gastric carcinogenesis via regulating COX-2 expression

Abstract: Helicobacter pylori (H. pylori) infection is the strongest risk factor for the initiation and progression of gastric cancer. However, the mechanism of H. pylori-induced pathogenesis remains unclear. In this study, we investigate the role of H. pylori infection in JMJD2B upregulation and the mechanism underlying gastric carcinogenesis. We find that JMJD2B can be induced by H. pylori infection via β-catenin pathway. β-catenin directly binds to JMJD2B promoter and stimulates JMJD2B expression following H. pylori … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…Herein, we have shown that possible downstream targets of NFκB and STAT3 pathways including TGFβ, HGF, IL‐6, IL‐8, TNC, collagens I and III were upregulated in fibroblasts infected by H. pylori (cagA+vacA+). We have also observed a significant induction of COX‐2 mRNA expression, which is closely associated with the formation and development of majority of gastric cancers 61, 62…”
Section: Discussionmentioning
confidence: 53%
“…Herein, we have shown that possible downstream targets of NFκB and STAT3 pathways including TGFβ, HGF, IL‐6, IL‐8, TNC, collagens I and III were upregulated in fibroblasts infected by H. pylori (cagA+vacA+). We have also observed a significant induction of COX‐2 mRNA expression, which is closely associated with the formation and development of majority of gastric cancers 61, 62…”
Section: Discussionmentioning
confidence: 53%
“…As one of the core factors of the Wnt signal pathway, β‐catenin widely exists in all kinds of cells and has multiple functions . β‐catenin mainly exists in the membrane of cells and to a lesser extent in the cytoplasm of cells.…”
Section: Discussionmentioning
confidence: 99%
“…KDM4B also upregulates miR‐125b expression and activates the Wnt signaling pathway . After Helicobacter pylori infection, KDM4B induced by the β‐catenin pathway along with nuclear factor‐κB (NF‐κB) binds to the cyclooxygenase‐2 (COX‐2) promoter to COX2 transcription . Expression levels of KDM4B and COX‐2 gradually increase in human gastric tissues during progression from infection‐related gastritis to gastric cancer.…”
Section: Altered Expression and Functions Of Kdm4s In Cancermentioning
confidence: 99%
“…102 After Helicobacter pylori infection, KDM4B induced by the β-catenin pathway along with nuclear factor-κB (NF-κB) binds to the cyclooxygenase-2 (COX-2) promoter to COX2 transcription. 103 Expression levels of KDM4B and COX-2 gradually increase in human gastric tissues during progression from infection-related gastritis to gastric cancer. Furthermore, KDM4B expression is positively correlated with COX-2 expression in both gastritis and gastric cancer tissues.…”
Section: Gastric Cancermentioning
confidence: 99%